Legal Aspects of the Marketing of Imported Used Clothes (Thrifting) in the Community Environment According to Business Law - Liani, Sesi Safitri; Nurfallah, M. Iip Wahyu (Faculty of Law, University of Dr. Soetomo, 2024)
The scope of clothing utilized for public sale or referred to as import items is examined in this study. Now that the issue has been resolved, the goal is to investigate how the legal system views business-related trading garments based on Indonesian trade clothes regulations and status laws. The study's methodology and research approach use method law and case studies. Results from customers' willingness to buy import-related clothing retailers were interviewed as part of the method of collection data employed. Studies show that factor pushers occur during activity marketing. There is still a public desire to purchase and select inexpensive and free clothing and a lack of knowledge about the negative effects. Importing clothing has its market. It is significant in Indonesia, thus importers and distributors view this industry as having business potential.